Α‐Conotoxin Bt1.8 from Conus betulinus selectively inhibits α6/α3β2β3 and α3β2 nicotinic acetylcholine receptor subtypes. Issue 1 (22nd June 2021) - Ning, Huying; Huang, Biling; Tae, Han‐Shen; Liu, Zhuguo; Yu, Shuo; Li, Liang; Zhang, Longxiao; Adams, David J.; Guo, Chenyun; Dai, Qiuyun
Abstract: α‐Conotoxins are small disulfide‐rich peptides found in the venom of marine cone snails and are potent antagonists of nicotinic acetylcholine receptors (nAChRs). They are valuable pharmacological tools and have potential therapeutic applications for the treatment of chronic pain or neurological diseases and disorders. In the present study, we synthesized and functionally characterized a novel α‐conotoxin Bt1.8, which was cloned from Conus betulinus . Bt1.8 selectively inhibited ACh‐evoked currents in Xenopus oocytes expressing rat(r) α6/α3β2β3 and rα3β2 nAChRs with an IC50 of 2.1 nM and 9.4 nM, respectively, and similar potency for human (h) α6/α3β2β3 and hα3β2 nAChRs. Additionally, Bt1.8 had higher binding affinity with a slower dissociation rate for the rα6/α3β2β3 subtype compared to rα3β2. The amino acid sequence of Bt1.8 is significantly different from other reported α‐conotoxins targeting the two nAChR subtypes. Further Alanine scanning analyses demonstrated that residues Ile9, Leu10, Asn11, Asn12 and Asn14 are critical for its inhibitory activity at the α6/α3β2β3 and α3β2 subtypes. Moreover, the NMR structure of Bt1.8 indicated the presence of a relatively larger hydrophobic zone than other α4/7‐conotoxins which may explain its potent inhibition at α6/α3β2β3 nAChRs. Abstract : Here we report α‐conotoxin Bt1.8 that selectively inhibit rat (r) α6/α3β2β3 and α3β2 nicotinic acetylcholine receptors (nAChRs) with an IC50 of 2.1 nM and 9.4 nM, respectively, and was relatively inactive at other rat nAChR subtypes. Bt1.8 also bound to rα6/α3β2β3 nAChR more tightly than rα3β2 nAChR with a slow dissociation rate compared to the latter. Structure‐activity analyses demonstrated the importance of the unique arrangement of amino acid residues in loop2 and the presence of a relatively large hydrophobic zone for its potency. This work provides new clues for the design of selective inhibitors of α6/α3β2β3 nAChRs to treat nicotine addiction and Parkinson's disease.